2021
DOI: 10.1111/jspn.12353
|View full text |Cite
|
Sign up to set email alerts
|

The health literacy disparity in adolescents with sickle cell disease

Abstract: Purpose: There are over 100,000 individuals with sickle cell disease (SCD) in the United States, most of whom are Black, poor, and publically insured. In combination with a chronic illness, these demographics lead to significant barriers to healthcare for patients with SCD, leaving them exceptionally vulnerable within the healthcare system. This unique vulnerability is especially notable when transitioning adolescents with SCD from pediatric to adult care, as this is a significant time of morbidity and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…While beyond the scope of this review, it is vital to note the intersection of general and health literacy for children and caregivers, 9 which impact comprehension of educational materials, adherence, and outcomes at all ages. [234][235][236][237][238] Children with reading difficulties are especially vulnerable to a lower understanding of their health condition, rationale for therapies, and treatment plans, which is likely to worsen with age as more is expected of them, particularly if literacy in family members is also low. This scenario is likely to impact the vital process of transitioning to self-care in adolescence and into adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While beyond the scope of this review, it is vital to note the intersection of general and health literacy for children and caregivers, 9 which impact comprehension of educational materials, adherence, and outcomes at all ages. [234][235][236][237][238] Children with reading difficulties are especially vulnerable to a lower understanding of their health condition, rationale for therapies, and treatment plans, which is likely to worsen with age as more is expected of them, particularly if literacy in family members is also low. This scenario is likely to impact the vital process of transitioning to self-care in adolescence and into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the intersection of general and health literacy in the context of medical complexity is currently under-studied, impacting treatment and transitioning strategies. 238 It is clear from this review that longitudinal research is needed applying an eco-biodevelopmental model where emergent literacy is framed as a distinct developmental domain reliant on efficient integration of the functional reading network. 239 This has the potential to align primary and specialty providers with educators and families across a range of conditions, 222 to optimize strategies and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy has not been explored extensively among adults living with SCD (McClure et al, 2016; Perry et al, 2017), but literacy levels are expected to impact their ability to attain, interpret, and apply such knowledge to manage SCD. Deficits in health literacy may be related to decreased self-efficacy (Mackey et al, 2016), and studies of adolescents with SCD have shown that individuals with SCD may be at risk for lower health literacy than the general population (Caldwell & Killingsworth, 2021).…”
Section: Relationships Among Social Determinants Of Health and Self-e...mentioning
confidence: 99%
“…Our target audience research identified a large proportion of low HL among patients with SCD and their caregivers. [1][2][3][4][5][6][7] Further investigation recognized interest among clinicians for the use of mobile health technologies in patients with SCD. 16 Step 3: Develop a concept for the product We used the Implementation Research Logic Model to conduct a series of iterative meetings to identify, design, and assess our solution strategy.…”
Section: Step 2: Conduct Target Audience Researchmentioning
confidence: 99%